Post-release Employment and Recidivism in Norway - Skardhamar, Torbjørn (Journal of quantitative criminology, 2012)
Objectives Investigate the transition from prison to employment and the relationship between post-release employment and recidivism. Methods We use a sample of every person released from Norwegian prisons in 2003 (N = 7,476), and they are followed through 2006 with monthly measures. We estimate the time to recidivism using discrete time survival models, conditioning upon both pre-release characteristics and post-release time-varying covariates (employment, educational enrollment and participation in labor market programs). Results The majority of former inmates were employed at some point in our data window, but it took approximately 30 months for 30% of them to become employed. The hazard of recidivism is substantially lower (0.12, p < .001) when former inmates are employed compared with unemployed, although observable individual characteristics can account for a large share of this association (0.50, p < .001, after adjustment). The negative association between employment and recidivism remains when controlling for other post-release statuses. Although post-release employment periods are associated with a lower risk of recidivism for all categories of principal offence, the magnitude of the association varies. The association is smaller for those receiving social benefits. Conclusion The findings are consistent with theories suggesting that employment reduces the risk of recidivism.